2020
DOI: 10.1177/0961203320938456
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on clinical and serological characteristics between patients with rhupus and those with systemic lupus erythematosus and rheumatoid arthritis

Abstract: Background The concomitant presence of two autoimmune diseases – systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) – in the same patient is known as rhupus. We evaluated a group of patients with rhupus to clarify further their clinical, serological and immunogenic features in a multi-centre cohort. In addition, the study aimed to explore the utility of the 2019 European League Against Rheumatism/American College of Rheumatology (EULAR/ACR) SLE classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
4
9
0
Order By: Relevance
“…Thus, our approach was coherent with the current view, supported by the presence of specific immunological biological markers of the 2 diseases. 1 Taken together, our data are concordant with those recently reported by Frade-Sosa et al 11 who found that the main clinical manifestations of rhupus were articular (94%), cutaneous (77.5%), and hematological (72.5%). The single difference was a lower prevalence of kidney involvement (10%), whereas ours was quite similar to that found in SLE (25%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, our approach was coherent with the current view, supported by the presence of specific immunological biological markers of the 2 diseases. 1 Taken together, our data are concordant with those recently reported by Frade-Sosa et al 11 who found that the main clinical manifestations of rhupus were articular (94%), cutaneous (77.5%), and hematological (72.5%). The single difference was a lower prevalence of kidney involvement (10%), whereas ours was quite similar to that found in SLE (25%).…”
Section: Discussionsupporting
confidence: 92%
“…The single difference was a lower prevalence of kidney involvement (10%), whereas ours was quite similar to that found in SLE (25%). 11 Regarding SLE, the profile of our patients, characterized by a longstanding disease with mainly articular pattern, satisfying both SLE sets of criteria or one of them, is in accordance with the findings of a recent study. 12 However, we cannot exclude induction of SLE manifestations by infliximab (n = 2) or etanercept (n = 1) prescribed in first line for 3 patients who had an initial diagnosis of RA before SLE occurrence.…”
Section: Discussionsupporting
confidence: 91%
“…In general, rhupus patients may present with any of the systemic manifestations of LE. However, a multicentric comparative study on clinical and serological characteristics between patients with rhupus and those with LE and RA reported that the main LE-like clinical manifestations in rhupus patients were cutaneous manifestations (oral ulcerations are among these), hematological manifestations, and serositis [26], so confirming data already reported by other investigators [3]. It is worth pointing out that these two studies had by far the most numerous casuistry.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies on rhupus patients revealed that RA symptoms and signs predominate over SLE-related organic damage, and the main symptom is erosive arthropathy [ 6 , 7 ]. However, it can manifest any of the typical SLE symptoms, including photosensitivity, serositis, vasculitis, or glomerulonephritis [ 6 ]. Unfortunately, the absence of official classification criteria places rhupus patients at a disadvantage and makes it challenging to classify them [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it can manifest any of the typical SLE symptoms, including photosensitivity, serositis, vasculitis, or glomerulonephritis [ 6 ]. Unfortunately, the absence of official classification criteria places rhupus patients at a disadvantage and makes it challenging to classify them [ 6 ]. In most cases, the prognosis of rhupus syndrome is determined by the degree of the organic damage, with a higher proportion having a worse long-term prognosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%